Perancangan Visual Identity Babsatu Coffee & Bakery di Payakumbuh - Muhammad Hazri Zein; Budiwirman Budiwirman (DEKAVE : Jurnal Desain Komunikasi Visual, 2021)
Babsatu Coffee & Bakery is a coffee shop located in Payakumbuh City owned by Ikhsan Marza. This cafe does not yet have a logo, so the logo is designed in the form of a colored logo and typography to represent the previous concept so that consumers and potential customers can easily remember it. The logo was formed based on the concept of Gestalt similarity logo theory or similarity in shape by using the shape of an owl as a topping, a cup as an owl's body and coasters as legs, followed by the letters of the name "chapter" itself, and using the word "Coffee & Bakery". “Like the title below, the shape fits well with a nice and modern shape. The design of Babsatu Coffee & Bakery's visual identity analysis is a SWOT (Strength, Weakness, Opportunity, Treatment) analysis to find solutions and problems. The design process begins by observing and interviewing the owner of Babsatu Coffee & Bakery to obtain the data needed to design this visual identity. The main media are in the form of brochures and supporting media in the form of posters, roll banners, business cards, T-shirts, stickers, paper bags, and cups. Keywords: Visual Identity, logo, babsatu coffee & bakery